Persepsi mahasiswa tentang kecurangan akademik di perguruan tinggi - Sasmika, Ayu; Daharnis, Daharnis (Counseling and Humanities Review, 2023)
Academic cheating is a behavior that must be avoided by students in carrying out the educational process in tertiary institutions in order to be able to honestly optimize their potential, interests and talents. However, the phenomenon found in the field is that there are still students who commit academic fraud. This study aims to describe students’ perceptions of academic cheating in the aspects of cheating, plagiarism, fabrication, and facilitating academic cheating. This study uses the quantitative descriptive method. The population in this study was 721 FIP UNP students in the 2018 entry year enrolled in the July-December 2022 semester, with a research sample of 261 students who were selected using an accidental sampling technique. Data is processed using descriptive statistical analysis. The results of the study on student perceptions of academic fraud as a whole are in the good category. In Other Words, Students perceive academic cheating as a negative behavior. In details: the cheating aspect is in the good category, the plagiarism aspect is in the good category, the fabrication aspect is in the good category, and the facilitating aspect is academic cheating are in the good category.